EFFECT OF CUTTING TOOL ON SURFACE ROUGHNESS OF WORKPIECE MATERIAL - Satish M.Rajmane; Jeevankumar A.Sodal (International Journal of Innovations in Engineering Research and Technology, 2021)
The cutting operation is nothing but removal of unnecessary material on workpiece by machining which includes operations like turning, facing, Grooving etc. Turning is one of material removal operation in which material from cylindrical workpiece is removed keeping Tool stationary & workpiece rotating. The cutting operation is affected by its cutting speed, feed & depth of cut. Also other factors like shape n geometry of Tool & coolant used have some effect over turning operation, which is done on either Conventional Lathe or CNC machine. The values of cutting speed, feed & depth of cut are responsible for the surface roughness of workpiece material after turning operation. Also they are responsible for rate of production & tool life. Because of this, these parameters needs to be optimized to achieve the best combination for achieving higher rate of production with the required surface finish of workpiece material which is the main objective.